2009
DOI: 10.1080/01443610902878783
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risk factors and effects of placental malaria in the UMTH, Maiduguri, North-eastern, Nigeria: A cross-sectional study

Abstract: Most of the adverse effects of malaria in pregnancy on the fetus are usually as a consequence of placental malaria (PM). This study was conducted with the objective of determining the prevalence, risk factors and pregnancy outcome of PM. A cross-sectional study of 437 pregnant women who delivered at the UMTH, Maiduguri was conducted between 24 July 2007 and 12 January 2008. Placental histology was done for the malaria parasite. Maternal packed cell volume was done and thick blood films were studied for the mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
26
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 14 publications
9
26
2
Order By: Relevance
“…The lower prevalence reported in this study may be due to the effective malaria control measures employed in the population, which include sulphadoxine -pyrimethamine 20 Several studies have shown that parity influences susceptibility to placental malaria with primigravidae being more susceptible compared to multigravidae. 19,24,25 In this study, higher parity did not confer any protection and this was consistent with the observations of Bako et al, 6 SuleOdu et al, 8 and Ofori et al 24 This finding was not surprising as same proportion of women across the various parities (nulliparous, primiparous and multiparous) used ITNs and also had at least 2 doses of IPT.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The lower prevalence reported in this study may be due to the effective malaria control measures employed in the population, which include sulphadoxine -pyrimethamine 20 Several studies have shown that parity influences susceptibility to placental malaria with primigravidae being more susceptible compared to multigravidae. 19,24,25 In this study, higher parity did not confer any protection and this was consistent with the observations of Bako et al, 6 SuleOdu et al, 8 and Ofori et al 24 This finding was not surprising as same proportion of women across the various parities (nulliparous, primiparous and multiparous) used ITNs and also had at least 2 doses of IPT.…”
Section: Discussionsupporting
confidence: 81%
“…Similar findings have been reported by Bako et al 6 and Gilles et al 26 in Maiduguri and Burkina Faso respectively. Some of the mothers might have cleared the peripheral parasitaemia at the time of delivery mostly due to the use of IPT and case management of malaria in pregnancy and such mothers had negative malaria parasite even in the presence of placental parasitaemia.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations